Iran [videorecording (DVD)] (Pilot Productions, 2007)
Visit the bustling capital city of Tehran before heading to the mountains to ski in Dizin. Travel onto Esfahan via the Caspian coast and Iran's most popular tourist Destination. The journey ends at the ancient city of Persepolis.